THE INFLUENCE OF FINANCIAL PERFORMANCE ON RETURNS WITH ESG AS AN INTERVENING VARIABLE - Iqbal Arraniri; Yasir Maulana; Munir Nur Komarudin; Wely Hadi Gunawan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The purpose of this study is to examine the effect of financial performance on stock returns by considering sustainability as an intermediate variable. This study uses Structural Equation Model analysis to assess the relationship between ROI, PER, PBV, and OPM variables as a representation of economic fundamentals, ESG variables as a representation of sustainability, and the relationship between Stock Return. The data used in this study are secondary data in the form of financial reports and accountability reports of public companies. The research sample consists of companies that meet the criteria set out in this study. The results of SEM analysis show that there is a significant direct influence between financial performance (ROI, PER, PBV, and OPM) and stock eturns and there is a significant direct influence between ROI, PER, PBV, and OPM and sustainability (ESG). In addition, this study also found that ESG acts as a mediator between economic fundamentals (ROI, PER, PBV, and OPM) and stock returns. The results of this study have important implications for understanding the relationship between economic fundamentals, sustainability and stock performance. This study provides empirical evidence that companies with good financial performance tend to adopt better sustainability practices, which in turn can affect stock returns. Business stakeholders, regulators and investors can use this impact to make more informed and sustainable decisions.